SISTEM PENDUKUNG KEPUTUSAN UNTUK MENENTUKAN TINGKAT KECERDASAN MAHASISWA DALAM PROSES PEMBELAJARAN MENGGUNAKAN METODE FUZZY ASSOCIATIVE MEMORY: Array - Syahriani, Budi (Universitas Harapan Medan, 2020)
As we know, the development of science, especially in the field of information technology, which is increasingly developing from year to year, in the field of information technology cannot be separated from the use of computers. Computers are a set of tools or machines that work systematically and function as electronic data processing tools that have the ability to be very fast and precise with very large quality. So STMIK Budidarma Medan, as an academic institution that is oriented towards science and information technology, establishes a curriculum that is flexible and able to accommodate existing developments. The author conducted a research at the Al-Hikmah Tanjung Balai Higher Education Foundation. From the research the writer carried out the stages and finally concluded and got the right title, namely: